DESKRIPSI KESEMPATAN BELAJAR LITERASI MATEMATIKA SISWA KELAS VIII TINGKAT SMP: DESCRIPTION OF OPPORTUNITIES TO LEARN MATHEMATICAL LITERACY FOR CLASS VIII JUNIOR HIGH SCHOOL LEVEL STUDENTS - Pemu, Nasrullah (KAMBIK: Journal of Mathematics Education, 2023)
This qualitative research with a descriptive approach aims to describe the learning opportunities provided and the mathematical literacy skills achieved by eighth-grade students at Public Junior High School 14 in Makassar. The subjects of the study were one teacher and 28 students. Data collection techniques included observation, tests, and interviews. The research instruments included observation sheets, tests of mathematical literacy skills, and interview guidelines. The data validation technique applied was source triangulation. The data analysis techniques in this study were: 1) data condensation, 2) data presentation, and 3) drawing conclusions. The results of the research showed that the learning opportunities provided by the teacher were not sufficient to support students' learning activities, including content coverage, content emphasis, content exposure, and the quality of instructional delivery. This had an impact on the students' achievement of mathematical literacy skills, which were still predominantly in the low category. Teachers need to innovate in the area of learning opportunities to support students with diverse abilities, capacities, and the availability of facilities that support learning activities.